Iatrogenic Displaced Maxillary Third Molar Tooth (Journal of KIST Medical College, 2020)
Minor to major complications may occur during the third molar extraction but should be optimized. Surgeons should know how to diagnose the case and manage the complications. We hereby report one of the rare complications of upper third molar extraction; iatrogenic displacement in infratemporal space. We emphasized hence on management of such technically sensitive case using 3D virtual surgical planning. The use of computer-assisted three-dimensional surgical planning to reconstruct the tooth in its localized position and orientation makes the operation more accurate, more convenient, and avoids damage to vital structures.